1994
DOI: 10.1021/bi00248a007
|View full text |Cite
|
Sign up to set email alerts
|

Location of M13 Coat Protein in Sodium Dodecyl Sulfate Micelles As Determined by NMR

Abstract: The major coat protein (gVIIIp) of bacteriophage M13 solubilized in sodium dodecyl sulfate (SDS) detergent micelles was used as a model system to study this protein in the lipid-bound form. In order to probe the position of gVIIIp relative to the SDS micelles, stearate was added, spin-labeled at the 5- or 16-position with a doxyl group containing a stable nitroxide radical. The average position of the spin-labels in the micelles was derived from the line broadening of the resonances in the 13C spectrum of SDS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
112
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 44 publications
(54 reference statements)
14
112
0
Order By: Relevance
“…The 5-doxylstearate spinlabel also has a significant effect on residues 36 and 37, while residue 38 is also influenced by 16-doxylstearate. These same effects have also been observed in a similar study on the location of gVIIIp in SDS micelles and several explanations have been suggested to account for these effects (Papavoine et al, 1994). In that study, a model was proposed in which the micellar environment around the C-terminal part of protein is distorted.…”
Section: The Location Of the Major Coat Protein In Dodpcho Micellessupporting
confidence: 74%
See 3 more Smart Citations
“…The 5-doxylstearate spinlabel also has a significant effect on residues 36 and 37, while residue 38 is also influenced by 16-doxylstearate. These same effects have also been observed in a similar study on the location of gVIIIp in SDS micelles and several explanations have been suggested to account for these effects (Papavoine et al, 1994). In that study, a model was proposed in which the micellar environment around the C-terminal part of protein is distorted.…”
Section: The Location Of the Major Coat Protein In Dodpcho Micellessupporting
confidence: 74%
“…The experiments performed to determine the location of gVIIIp in the DodPCho micelles have been described in detail in an earlier paper (Papavoine et al, 1994). Two detergent-like spin-labelled compounds were used, 5-doxylstearate and 16-doxylstearate (Aldrich), which were solubilized in [2H,]methano1 (Merck) to a final concentration of 0.1 M. The spin-labels differ in the location of the nitroxide radical relative to the alkyl chain of the stearate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has established that the 5-doxy1 moiety of the lipid 5-doxy1 stearic acid is located close to the surface of both SDS and DPC micelles (Brown, 1981;Mendz et al, 1988Mendz et al, , 1991Papavoine et al, 1994;Van den Hooven et al, 1996). The unpaired electron of the spin label broadens protons within -15 A sphere via electron-dipole nuclear-dipole interactions.…”
mentioning
confidence: 97%